Artificial boundaries? Shaping policy through empowering research. Issue 4 (2nd October 2022) - O'Keeffe, Suzanne
Abstract : This paper is about the politics of policy knowledge production. It calls for spaces to be forged to allow teachers' voices to have centre stage in knowledge creation and production. Specifically, this paper discusses the need for alternative ways of conducting educational research so that power in research design is utilised as a capacity for change. First, the politics of knowledge production is explored. The second and most central task of this paper is to highlight the role that teachers' knowledge can play in shaping education policy through emancipatory research practices. Overall, this paper advocates that the time has arrived for a fresh look at teachers' participation in the production and validation of knowledge. Valuing teachers' embodied knowledge and the unique position teachers hold within the education system, this paper is a window on the present, and suggests the direction the conversation should take in order to move education policy beyond the endless accumulation of evidence towards impactful change.